Diffraction radiation of a particle passing by an impedance wedge - Ostroushko, V.M. (Вопросы атомной науки и техники, 2021)
The diffraction radiation field generated by the charged particle passing by the perfectly conductive or impedance wedge is considered. With perfect conductivity, the wedge rotation around the edge fixed along with the straight particle motion line, does not change the total radiated energy. When the motion to the edge is almost parallel to a face of wedge then an increase of impedance from zero increases the radiated energy.